Consolidated Group of Taxpayers: Infusion into the Russian Economic Practice - Kondrashova, Natalia A. (International Journal of Economics and Financial Issues, 2016)
The article analyses the process of introduction of the consolidated taxation mechanism in Russia. The main purpose of the study is to conduct an assessment of the impact of consolidated groups of taxpayers on the national economy, including intergovernmental relations. Author further identifies the features and areas of further development of the consolidated taxation mechanism in the country. A four-year period of activity of consolidated groups in Russia is taken for analysis, giving the opportunity to evaluate the results, to draw first conclusions, and allocate the problems associated with the subsequent planning and forecasting of these activities. Certain trends in application of new economic tools of the tax regulation are identified. Keywords: consolidated tax group, income tax, corporate income tax, regional budget, regional economy JEL Classifications: A12, H22, R22